2018
DOI: 10.3389/fphys.2018.01315
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidic Acid Is Associated With Cardiac Dysfunction and Hypertrophy by Suppressing Autophagy via the LPA3/AKT/mTOR Pathway

Abstract: Background: Lysophosphatidic acid (LPA), as a phospholipid signal molecule, participates in the regulation of various biological functions. Our previous study demonstrated that LPA induces cardiomyocyte hypertrophy in vitro; however, the functional role of LPA in the post-infarct heart remains unknown. Growing evidence has demonstrated that autophagy is involved in regulation of cardiac hypertrophy. The aim of the current work was to investigate the effects of LPA on cardiac function and hypertrophy during myo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 58 publications
2
14
0
Order By: Relevance
“…Present findings showed blockage of autotatxin inhibited high-fat diet-induced cardiac hypertrophy, including reduction of heart weight, cell size, left ventricular dimension and left ventricular mass in obese mice. The LPA3/AKT/mTOR pathway was a potential signaling pathway in modulating cardiac hypertrophy (Yang et al 2018). Consistent with the role of autotaxin in pulmonary fibrosis (Ninou et al 2018), present study found autotaxin also participated in cardiac fibrosis.…”
Section: Discussionsupporting
confidence: 86%
“…Present findings showed blockage of autotatxin inhibited high-fat diet-induced cardiac hypertrophy, including reduction of heart weight, cell size, left ventricular dimension and left ventricular mass in obese mice. The LPA3/AKT/mTOR pathway was a potential signaling pathway in modulating cardiac hypertrophy (Yang et al 2018). Consistent with the role of autotaxin in pulmonary fibrosis (Ninou et al 2018), present study found autotaxin also participated in cardiac fibrosis.…”
Section: Discussionsupporting
confidence: 86%
“…Moreover, protection from cardiac hypertrophy was also associated with an attenuation of systolic dysfunction and cardiac dilatation [35]. In primary mouse cardiomyocytes, LPA administration increased proinflammatory and prohypertrophic gene expression, suggesting that LPA directly induces cardiac inflammation and hypertrophy [35], in agreement with other work demonstrating that LPA induces hypertrophic remodeling in neonatal rat ventricular cardiomyocytes [81] and H9C2 cells, and following myocardial infarction in mice in vivo [82]. Interestingly, in humans, circulating ATX levels correlated inversely with ejection fraction and positively with the hypertrophy marker, NT-proBNP, indicating that the ATX-LPA axis may also contribute to obesity-induced cardiomyopathy in humans [35].…”
Section: Studies Using Pharmacological Lpa Receptor and Atx Modulators And In Situ Atx Silencingsupporting
confidence: 88%
“…Intriguingly, the enhanced cardiomyocyte autophagy is reported to be mediated by the PI3K/AKT/mTOR signaling pathway [ 38 ]. Previous work has reported that PI3K/AKT pathway activation is pathogenic in cardiac dysfunction and hypertrophy [ 39 ]. Moreover, a study reported that Iva prevented cardiac hypertrophy and fibrosis via inhibiting PI3K/AKT/mTOR pathway in an established transverse aortic constriction mouse model [ 40 ].…”
Section: Discussionmentioning
confidence: 99%